Pengaruh Agresivitas Pajak, Beban Pajak Tangguhan, dan Kebijakan Utang terhadap Nilai Perusahaan - Dian Nur Aprida; Aris Sanulika (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
This research aims to examine the influence of tax aggressiveness, deferred tax burden and debt policy on company value in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) in the 2018-2022 period. In this research, the dependent variable is used, namely Company Value (Y) and independent variables, namely Tax Aggressiveness (X1), Deferred Tax Burden (X2), Debt Policy (X3). This research uses financial reports of companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. The population in this study is 125 non-cyclical consumer companies listed on the Indonesia Stock Exchange in the 2018-2022 period. The sample selection technique used a purposive sampling method, the samples obtained were 34 companies with 170 observation data. The data source uses quantitative method secondary data. The analysis technique used is multiple linear regression with the help of the eviews 10 application program. Based on the test results, this research states that 1) Tax aggressiveness has no effect on company value, 2) Deferred tax burden has an effect on company value, 3) Debt policy has no effect on the value of the company.